Lifestyle correlates of musical preference: 2. Media, leisure time and music - North, Adrian; Hargreaves, David (Sage Publications Ltd., 2007)
Several studies indicate that musical preferences provide a means of discriminating between social groups, and suggest indirectly that musical preferences should correlate with a variety of different lifestyle choices. In this study, 2532 participants responded to a questionnaire asking them to state their musical preference and also to provide data on various aspects of their lifestyle (namely media preferences, leisure interests and music usage). Numerous associations existed between musical preference and these aspects of participants’ lifestyle. The nature of these associations was consistent in part with previous research on taste publics concerning the high-culture–low-culture divide, such that fans of ‘high-art’ and ‘low-art’ musical styles demonstrated a preference for other ‘high-art’ and ‘low-art’ media objects respectively, as reflected in reading, TV and radio preferences, and leisure activities.